Evaluasi Kualitas Layanan Informasi Website Universitas Brawijaya Terhadap Kepuasan Pengguna Menggunakan Model E-S-Qual dan E-Recs-Qual - Mochammad Valdi Fuadi; Ari Kusyanti; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Brawijaya University website information service is an important aspect for Brawijaya University in providing information to its users. The concept of good quality of information services and according to user needs will affect user satisfaction and perceived value. This research uses conceptual model from E-S-Qual and E-Recs-Qual to measure the quality of website information service of Brawijaya University and to know the effect of the model on user satisfaction and perceived value. The measurement of the quality of Brawijaya University website information service uses 8 variables from E-S-Qual and E-Recs-Qual including Efficiency, System Availability, Privacy, Fulfillment, Web Appearance, Personalization, Responsiveness, and Contact. This study also provides recommendations using the ISO / IEC 9126 standard. This study uses the population of Brawijaya University students with a sample of 310 respondents. Methods of data collection of this research is by distributing questionnaires to respondents. Correlation analysis techniques and correlation strength between latent variables or constructs using Structural Equation Modeling (SEM). The results showed that the variables system availability and contact is a variable that has no effect on user satisfaction and perceived value due to these variables produce a critical ratio value of less than 1.96 at the stage structural fit model.